2015
DOI: 10.1159/000439584
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine in Combination with Metoprolol Improves Symptoms and Quality of Life in Patients with Stable Angina Pectoris: A post hoc Analysis from the ADDITIONS Trial

Abstract: Objectives: Elevated heart rate can increase myocardial oxygen demand and reduce myocardial perfusion, provoking myocardial ischemia and angina symptoms. We evaluated adding ivabradine to the therapy of patients on metoprolol. Methods: ADDITIONS (prActical Daily efficacy anD safety of Procoralan® In combinaTION with betablockerS) was a multicenter, 4-month, noninterventional, prospective, open-label trial that involved stable-angina patients. Along with metoprolol, patients received ivabradine (5 or 7.5 mg, b.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…Ivabradine on top of metoprolol led to a significant improvement in QoL, improving the VAS scale score by 14.7 points. Similar results were obtained in another study assessing the combination of ivabradine with metoprolol where VAS scale score was improved by 14.1 points . Adding ivabradine to the treatment plan improved all treadmill exercise tolerance test criteria and by restoring a satisfactory level of usual activities also improved QoL in those patients .…”
Section: Discussionsupporting
confidence: 80%
“…Ivabradine on top of metoprolol led to a significant improvement in QoL, improving the VAS scale score by 14.7 points. Similar results were obtained in another study assessing the combination of ivabradine with metoprolol where VAS scale score was improved by 14.1 points . Adding ivabradine to the treatment plan improved all treadmill exercise tolerance test criteria and by restoring a satisfactory level of usual activities also improved QoL in those patients .…”
Section: Discussionsupporting
confidence: 80%
“…As previously shown, ivabradine significantly improved quality of life parameters in the whole population as well as in patients with previous PCI and with concomitant metoprolol medication [18,21,22]. Here, we extend the findings to a larger range of patient subgroups, where ivabradine showed consistent improvement in quality of life, using both measurement systems, in all considered subgroups (absolute changes from baseline ranging from 0.11 ± 0.18 to 0.26 ± 0.28 for EQ-5D index and from 6.3 ± 9.60 to 16.2 ± 16.94 for EQ VAS score; p < 0.0001 for all changes).…”
Section: Resultsmentioning
confidence: 84%
“…In our study, the baseline characteristics of the population were comparable to those of three other prospective, observational cohort studies successfully testing the concept of (free) combination of beta-blockers with ivabradine in real-life populations, e.g., the ADDITIONS [ 21 ], REDUCTION (Reduction of ischemic Events by reDUCtion of heart rate In treatment Of stable aNgina with ivabradine) [ 22 ], and RESPONSIfVE (Evaluation of effectiveness and therapeutic response to ivabradine in daily practical use for chronic stable angina patients) study [ 23 ], with the exception of a slightly lower HR and angina frequency at study entry, which can be mainly explained by the high percentage of patients not only being pre-treated with beta-blocker but as well with ivabradine in the current study. A subgroup analysis of the ADDITIONS trial and post hoc analysis of the above-mentioned three non-interventional studies had consistently revealed a pronounced further reduction of HR, weekly angina attacks and nitrate consumption, respectively, as well as an improvement of exercise capacity and health-related quality of life (QoL) after 4 months of therapy with the free combination of metoprolol and ivabradine [ 24 , 25 ]. At last follow-up, the results obtained with the new metoprolol/ivabradine FDC in terms of heart rate (67 bpm), frequency of angina attacks per week (0.3), weekly short-acting nitrate use (0.2 unit) and CCS class distribution were nearly identical to those with the free combination of both drugs in, e.g., the aforementioned ADDITIONS subgroup analysis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in three large observational studies with stable AP patients in daily routine practice [ 21 23 ]. In particular, a post hoc analysis of the ADDITIONS (prActical Daily efficacy anD safety of ivabradine In combinaTION with beta-blockerS) study as well as a pooled analysis of these three observational cohorts have proven beneficial effects for adding ivabradine to an existing therapy with the most commonly prescribed beta-blocker metoprolol in real-life populations of stable CAD patients [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%